2018
DOI: 10.5206/cjsotl-rcacea.2018.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Turnitin® Use at a Canadian University

Abstract: While the text-matching tool, Turnitin®, has traditionally been used to deter and detect plagiarism, more recently, instructors have started to use this tool for formative self-assessment. To describe Turnitin®’s use in practice and to explore perceptions of this tool, we surveyed 940 students, teaching assistants, and instructors at a Canadian university. Our findings indicate that Turnitin® was more commonly used for plagiarism detection than for formative self-assessment. The majority of respondents had pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Compared to other countries, Canada has been slow to adopt TMS in higher education (Bretag 2019b;Kloda and Nicholson 2005;Strawczynski 2004;Zaza and McKenzie 2018). This study demonstrates that the software offers some value to a variety of stakeholders in post-secondary institutions by providing students with examples of do's and don'ts while writing a manuscript.…”
Section: Implications For Policy and Practicementioning
confidence: 83%
See 3 more Smart Citations
“…Compared to other countries, Canada has been slow to adopt TMS in higher education (Bretag 2019b;Kloda and Nicholson 2005;Strawczynski 2004;Zaza and McKenzie 2018). This study demonstrates that the software offers some value to a variety of stakeholders in post-secondary institutions by providing students with examples of do's and don'ts while writing a manuscript.…”
Section: Implications For Policy and Practicementioning
confidence: 83%
“…A key point of interest was that students reported that academic staff could have better explained the software and what to do if the software found a text match. Although respondents were generally satisfied with the TMS, it was found that students needed more information and support from their instructors to use it more effectively (Zaza and McKenzie 2018).…”
Section: Text-matching Softwarementioning
confidence: 98%
See 2 more Smart Citations
“…The results of this case set a legal precedent in Canada regarding the use of text-matching software in Canada, with the long-term impact being that such software is not used in Canada to the extent that it is in other countries. There has also been limited research into how text-matching software is used in Canadian universities (for one example see Zaza & McKenzie, 2018) in part because universities have firmly limited their use of these products or declined to use them all together.…”
Section: The Creative Disruption Era: 1992-2019mentioning
confidence: 99%